2004
DOI: 10.4049/jimmunol.172.10.6152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Makeup of theDRRegion in Rhesus Macaques: Gene Content, Transcripts, and Pseudogenes

Abstract: In the human population, five major HLA-DRB haplotypes have been identified, whereas the situation in rhesus macaques (Macaca mulatta) is radically different. At least 30 Mamu-DRB region configurations, displaying polymorphism with regard to number and combination of DRB loci present per haplotype, have been characterized. Until now, Mamu-DRB region genes have been studied mainly by genomic sequencing of polymorphic exon 2 segments. However, relatively little is known about the expression status of these genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…Mhc class I group 1 and group 2 configurations were also linked to Mhc class II haplotypes expressing two DRB genes, namely Mamu-DQB1*1801-DRB1*0303-DRB1*1007 and Mamu-DQB1*1811-DRB1*0406-DRB5*0301. 37 One of them (Mamu-DQB1*1801-DRB1*0303-DRB1*1007) was also linked to class I configurations associated with slow disease progression, including configuration 4. This finding indicates that Mhc class I genotypes have a much more marked influence upon disease progression than class II genotypes, thereby corroborating previous reports on HIV-infected humans 20 and SIV-infected macaques.…”
Section: Contribution Of Mhc Class II Genotypes To Survival Timementioning
confidence: 99%
“…Mhc class I group 1 and group 2 configurations were also linked to Mhc class II haplotypes expressing two DRB genes, namely Mamu-DQB1*1801-DRB1*0303-DRB1*1007 and Mamu-DQB1*1811-DRB1*0406-DRB5*0301. 37 One of them (Mamu-DQB1*1801-DRB1*0303-DRB1*1007) was also linked to class I configurations associated with slow disease progression, including configuration 4. This finding indicates that Mhc class I genotypes have a much more marked influence upon disease progression than class II genotypes, thereby corroborating previous reports on HIV-infected humans 20 and SIV-infected macaques.…”
Section: Contribution Of Mhc Class II Genotypes To Survival Timementioning
confidence: 99%
“…Both of these alleles were present at a frequency of 44% in the EC cohort but were present only at a frequency of less than 23% in the entire SIV-infected cohort (P values of 0.05 and 0.02 for Mamu-DRB1*0306 and Mamu-DRB1*1003, respectively) ( Table 3). Previously de Groot et al (9) showed that these two MHC-II alleles segregate together along with Mamu-DRA1*01041 as part of the same genetic configuration.…”
Section: Vol 82 2008 Mhc-ii Alleles Enriched In Siv-infected Ec Macmentioning
confidence: 99%
“…PCR mixtures and conditions were as described in ref. 38, employing a commercially available Taq polymerase (Invitrogen). RT-PCR was performed directly on RNA by using the Qiagen OneStep RT-PCR kit according to the manufacturer's guidelines.…”
Section: Dna͞rna Isolation and Exon 2 Amplification Of Genomic Dnamentioning
confidence: 99%